2000
DOI: 10.1038/sj.jea.7500103
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticide exposure in rural and urban areas in Mexico

Abstract: The objective of this study was to determine the level of organochlorine pesticides in maternal milk of women living in urban and rural areas in central Mexico. High levels of the DDT ( 1,1,1 -trichloro -2,2 -bis ( p -chlorophenyl ) ethane ) and metabolites, p,p H -DDT ( 1.83, 0.66 and 3.13 mg / kg ) and p,p H -DDE ( 2.49, 4.28 and 13.32 mg / kg ) , were encountered for Mexico City, Cuernavaca and rural Morelos, respectively. As was expected, the highest levels of exposure to these pesticides were found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…17,23,35 In fact, the p,p'-DDT and p,p'-DDE levels reported for the women in this study exceed levels reported for women from Mexico City collected in 1989 to 1990, prior to the restriction of DDT use. 4 The levels reported for participants in this study are in the range of those reported during the same period (1997)(1998) in pregnant women in other coastal areas of Mexico, [25][26][27] such as Veracruz, where direct exposure to DDT was more likely to occur than in more urban areas. In contrast, as evidence of the decreasing amount of DDT used in Mexico, the levels of p,p'-DDT and p,p'-DDE reported here are lower than those reported from rural Morelos in 1989 to 1990, before DDT use was severely restricted.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…17,23,35 In fact, the p,p'-DDT and p,p'-DDE levels reported for the women in this study exceed levels reported for women from Mexico City collected in 1989 to 1990, prior to the restriction of DDT use. 4 The levels reported for participants in this study are in the range of those reported during the same period (1997)(1998) in pregnant women in other coastal areas of Mexico, [25][26][27] such as Veracruz, where direct exposure to DDT was more likely to occur than in more urban areas. In contrast, as evidence of the decreasing amount of DDT used in Mexico, the levels of p,p'-DDT and p,p'-DDE reported here are lower than those reported from rural Morelos in 1989 to 1990, before DDT use was severely restricted.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, as evidence of the decreasing amount of DDT used in Mexico, the levels of p,p'-DDT and p,p'-DDE reported here are lower than those reported from rural Morelos in 1989 to 1990, before DDT use was severely restricted. 4 Moreover, the levels reported here are roughly twice those reported from samples collected in 2003 from the same area (p,p'-DDT, median ϭ 241 ng/g; p,p'-DDE, median ϭ 2,695 ng/g) (Hernandez-Avila, personal communication). The serum p,p'-DDT and p,p'-DDE levels reported in this study 36 are on the order of those reported more than 40 yr ago in the United States (p,p'-DDT, median ϭ 1,362 ng/g; p,p'-DDE, median ϭ 5,119 ng/g) and are higher than those reported for Mexican-American women in the United States today (median ϭ p,p'-DDT Ͻ10 ng/g, median ϭ p,p'-DDE 623 ng/g).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The concentrations found (DDT: 15.6-28.8 ppb in blood, 162-4840 ppb in breast milk, 10-9030 ppb in adipose tissue; o, p′-DDT: b0.7-4.7 ppb in blood; 138 ppb in breast milk) (Elvia et al, 2000;Minelli and Ribeiro, 1996;Torres-Arreola et al, 1999;Waliszewski et al, 2001) in the human body are lower than the EC 50 determined in this study for DDT, and o,p′-DDT, but considering the pharmacological effect of these two compounds on estrogen receptors, they can induce, albeit partially, the conformational change required for the transcriptional activation to occur in the ligand-binding domain. In addition, we are exposed to a multitude of agents with estrogen-like activity, which are capable of accumulating in adipose tissue and are present in blood serum.…”
Section: Discussionmentioning
confidence: 98%